Enzymatic Hydrolysis of Soy Protein Isolates : DSC study - Molina Ortiz, Sara E. (2001)
The aim of this work was to analyze the possible use of differential scanning calorimetry (DSC) as a method to study the process of protein modifications during enzymatic hydrolysis. Results of the enzymatic hydrolysis of soy protein showed significant differences in the values of maximum deflection temperature (Tp), heat of reaction (ΔH), and width at half peak height (ΔT1/2), between DSC curves corresponding to the substrate, or zerotime of hydrolysis, and those of the hydrolysates obtained by the action of cucurbita and pomiferin enzymes. DSC curve changes mentioned were explained by the use of gel-filtration chromatography, denaturing electrophoresis and surface hydrophobicity of the hydrolysis products obtained at 30 min of reaction.